Epiphanius of Cyprus : A Cultural Biography of Late Antiquity - Jacobs, Andrew S., 1973- (Book collections on Project MUSE., 2016)
"Epiphanius, Bishop of Contantia on Cyprus from 367-403 C.E., was incredibly influential in the last decades of the fourth century, yet modern scholarship has very little use for him. His major surviving text (the Panarion, an encyclopedia of heresies) is plumbed for lost sources, but Epiphanius himself is often dismissed as an anti-intellectual crank, a marginal figure of late antiquity. This book moves Epiphanius from the margin back toward the center, and proposes we view major cultural themes of late antiquity in a new light altogether. Through an examination of key cultural concepts--celebrity, conversion, discipline, scripture, salvation--this book shifts our understanding of 'late antiquity' from a transformational period open to new ideas and peoples toward a Christian Empire that posited a troubling, but ever-present, 'otherness' at the center of its cultural production. The book includes a consideration of the hagiographic 'afterlives' of Epiphanius, and concludes with a discussion of why modern scholarship finds the fourth-century bishop so troubling"--Provided by publisher.